2014
DOI: 10.1194/jlr.m040071
|View full text |Cite
|
Sign up to set email alerts
|

Key intestinal genes involved in lipoprotein metabolism are downregulated in dyslipidemic men with insulin resistance

Abstract: Dyslipidemia is an important feature of insulin resistance (IR) that contributes to the pathogenesis of atherosclerosis and increases the risk of cardiovascular disease ( 1 ). Dyslipidemia associated with IR is typically characterized by elevated concentrations of triglyceride-rich lipoproteins (TRLs), reduced plasma levels of HDL-cholesterol (HDL-C), an increased number of small dense LDL particles, and greater levels of free fatty acid (FFA) ( 1 ). Metabolic kinetic studies have indicated that the increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…The increased production rate (PR) of both hepatic apolipoprotein (apo) B-100-containing lipoproteins and intestinally derived apoB-48-containing TRLs, as well as the reduced catabolism of these subfractions, cause the overaccumulation of TRLs associated with IR (4). Recently, our group also showed that subjects with IR present important alterations in the expression of key intestinal genes involved in lipoprotein homeostasis that could play a role in the overall dysregulation of TRL metabolism (5). This is of significant interest because atherogenic dyslipidemia is undisputedly a major CVD risk factor for populations with IR (6,7).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The increased production rate (PR) of both hepatic apolipoprotein (apo) B-100-containing lipoproteins and intestinally derived apoB-48-containing TRLs, as well as the reduced catabolism of these subfractions, cause the overaccumulation of TRLs associated with IR (4). Recently, our group also showed that subjects with IR present important alterations in the expression of key intestinal genes involved in lipoprotein homeostasis that could play a role in the overall dysregulation of TRL metabolism (5). This is of significant interest because atherogenic dyslipidemia is undisputedly a major CVD risk factor for populations with IR (6,7).…”
Section: Introductionmentioning
confidence: 90%
“…However, the consumption of various types of dietary fat, including MUFAs, PUFAs, ω-3 PUFAs, SFAs, and mediumchain TGs, has also been reported to have a very limited impact on TRL apoB-48 metabolism and postprandial lipemia in subjects with IR (18,23,30,31). It is well recognized that VLDL apoB-100 PS and insulin sensitivity are the principal determinants of the overproduction of TRL apoB-48 in dyslipidemic and IR subjects (5,32). In this context, the absence of impact of ω-6 PUFAs on TRL apoB-48 metabolism may result from the neutral effect of ω-6 PUFA on VLDL apoB-100 PS and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results and conclusions are strongly supported by the findings of increased de novo lipogenesis rate, increased expression of L-FABP, higher abundance of MTP protein expression, and reduced proteasomal degradation of Apo B-48 in the small intestine of insulin-resistant animals. 6,8 Therefore, the present study presents possible mechanisms filling the gap between human in vivo observation [17][18][19] and the detailed characterization of intestinal metabolism performed in animal models of IR. [6][7][8][10][11][12][13][14][15] In addition to these defects related to lipid metabolism and TRL production, we reported several molecular alterations indicating the presence of an aberrant intestinal cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…16 Only few studies have confronted the relevant issue of these important findings to humans as did the pioneering work of Lewis' group, using stable isotope tracer infusion. [17][18][19] They have shown an association between the increase in apolipoprotein (Apo) B-48-containing lipoproteins and IR in humans. 17,18 Nevertheless, the link between this exaggerated assembly and secretion of TLR and in situ IR in the gut is not yet fully understood.…”
mentioning
confidence: 99%